VHH antibody targeting the chemokine receptor CX3CR1 inhibits progression of atherosclerosis. Issue 1 (1st January 2020) - Low, Sarah; Wu, Haixia; Jerath, Kavita; Tibolla, Annette; Fogal, Birgit; Conrad, Rebecca; MacDougall, Margit; Kerr, Steven; Berger, Valentina; Dave, Rajvee; Villalona, Jorge; Pantages, Lynn; et al.
ABSTRACT: CX3CR1 has been identified as a highly attractive target for several therapeutic interventions. Despite this potential, no potent antagonists, either small molecule or monoclonal antibody, have been identified. Here we describe the lead finding and engineering approach that lead to the identification of BI 655088, a potent biotherapeutic antagonist to CX3CR1. BI 655088 is a potent CX3CR1 antagonist that, upon therapeutic dosing, significantly inhibits plaque progression in the standard mouse model of atherosclerosis. BI 655088 represents a novel and highly selective biotherapeutic that could reduce inflammation in the atherosclerotic plaque when added to standard of care treatment including statins, which could result in a significant decrease in atherothrombotic events in patients with existing cardiovascular disease.